2014
DOI: 10.14245/kjs.2014.11.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Rod into Retroperitoneal Region: A Case Report and Review of the Literature

Abstract: Spinal stabilization with fusion is the widely used method for traumatic or pathologic fracture of spine, spinal stenosis, and spondylolisthesis. Complications may emerge during or after the operations. Infection, hematoma and neurological deficits are early noticed findings. Screw and/or rod fractures present in long-term after surgery. Rod migration in out of the spinal column is a rare entity. A 67-year-old woman was visited our clinic for right leg pain. She had a previous spinal instrumentation surgery fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…In addition, there were no signs of eccentric coupling between the nut and screw head intra-operatively at the index surgeries or at the times of revision. Although it has been reported that these rods can get loose and migrate leaving behind a tight and properly placed pedicle screw caps without evidence of loosening (7) , in our cases, the screw caps were loose and backed-off by one or two turns. It is unclear why the caps got loose although after experience with the first case, additional time was spent ensuring that the torque applied to the caps was of sufficient amount as prescribed by the manufacturer.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In addition, there were no signs of eccentric coupling between the nut and screw head intra-operatively at the index surgeries or at the times of revision. Although it has been reported that these rods can get loose and migrate leaving behind a tight and properly placed pedicle screw caps without evidence of loosening (7) , in our cases, the screw caps were loose and backed-off by one or two turns. It is unclear why the caps got loose although after experience with the first case, additional time was spent ensuring that the torque applied to the caps was of sufficient amount as prescribed by the manufacturer.…”
Section: Discussioncontrasting
confidence: 65%
“…Leute et al (9) reported a case of set screw fracture with cage dislocation after an open TLIF procedure, they acknowledged this as malpositioning of set screws or flaws in their production. In another case by Bayri et al (7) , a patient, who had underwent spinal instrumentation surgery for spondylolisthesis 6 years ago, was detected to have migration of rod into retroperitoneal region, the reason for movement of the rod in this case was due to unbalanced motion at the instrumented level without any fusion. This type of implant failure may be secondary to several reasons: technique related, implant design defects, patient related factors and material failure with or without a non-rigid fixation (pseudoarthrosis).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the exact soft tissue track of the migrated rod is not known and the patient was fortunate to not have developed skin or soft tissue complications such as a chronic or infected sinus tract formation. In a literature review of rod migration by Bayri et al [ 8 ], all cases necessitated surgical intervention for rod removal, apart from those cases where the patients declined surgery. Our case is unique and the first in the literature to have extruded from the soft tissue spontaneously, without the need for surgical removal.…”
Section: Discussionmentioning
confidence: 99%
“…Distal rod migration remains uncommon and has been reported in a variety of anatomical locations, including the retroperitoneal region, the knee, and the pelvis. 1,2,3 It is postulated that spinal fixation without fusion might allow the mechanical system some vulnerability to motion effects of the spine. Bilateral distal rod migration is rarer still.…”
mentioning
confidence: 99%